MEANS OF EXPRESSING THE NATIONAL CHARACTER - Jumayeva Shahlo Shokirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
One of the most urgent issues of modern translation theory is to preserve the original content of the translated text, to present the era, people, social environment, physical and mental state of characters, thoughts, nationality, aesthetic information as in the original work, in addition, to study the problems of preserving the style and originality of the writer in translation and presenting it to the reader. In this article the author talks about the peculiarities of translation of prose work.